Assessment of Drought Tolerance of Two Cultivars of Indian Mustard (Brassica juncea) Using Morphological and Physiological Parameters - Preeti Rani; Jyoti Rani; Alisha Mittal; Narender Sheoran (Archives of Current Research International, 2024)
Aims: Drought stress may affect the Morphology, biochemistry, growth, and physiology of Brassica juncea (Indian mustard), a low-cost, oil-yielding, and economically significant plant. In this paper assessing various growth, morphological, and physiological parameters under different irrigation regimes could offer some significant information for the selection of a suitable and appropriate genotype for breeding. Study Design: Two commonly grown cultivars (RH-725 and RH-749) of mustard in Haryana under four irrigation regimes were evaluated. The applied Irrigation regimes were: control (double irrigation: once at the 50% flowering and another at the 50% fruiting stages), early irrigation (at 50% flowering only), late irrigation (at 50% fruiting only), and stress (no irrigation). The plants were exposed to short-term water shortages during the vegetative and reproductive growth stages. Drought stress in both stages had a negative effect on the morphological and physiological parameters of mustard. Place and Duration of Study: An open field experiment was performed at the Nursery of Kurukshetra University, Kurukshetra, Haryana, India, located at the latitude of 290–95° north and longitude of 760–82° east, with a height of 258.4 m above sea level. Crop sown under field conditions from October to March for two consecutive years (2018-2019, 2019-2020) at a temperature of 30-32 °C (days) and 15-25 °C (nights). Methodology: Measured adaptability using 15 morphological, 4 physiological, and 7 different growth parameters. PCA data revealed that physiological and growth parameters are more sensitive than morphological parameters in distinguishing the control and drought treatments. Alterations in physiological parameters occurred at all three levels of water stress. Growth analysis and yield parameters decreased with the severity of stress. Drought-stress treatments gradually reduced the Morphological and physiological traits of mustard. Results: The study revealed a relationship between Brassica species’ adaptation to drought stress and the rapidity, severity, and duration of the drought event. This highlights the importance of considering these factors while selecting genotypes for breeding programmes aimed at improving drought tolerance in B. juncea. Overall, the research provides valuable information for selecting suitable and appropriate genotypes for breeding drought-tolerant varieties of B. juncea. By understanding the specific physiological (relative water content, leaf osmotic potential, membrane stability index, electrolytic index) and growth parameters (plant height, root length, fresh and dry weight of leaves and roots, leaf area etc.) that are more sensitive to drought stress. Furthermore, this study revealed a relationship between Brassica species’ adaptation to drought stress and the rapidity, severity, and duration of the drought event. Based on PCA values, the cultivar RH-749 performed better both morphologically and physiologically under all stress conditions compared to RH-725. This suggests that RH-749 is more adapted and tolerant to drought stress, making it a potential candidate for breeding and cultivation in water-limited environments.